PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VIII.6 SMP NEGERI 7 DENPASAR TAHUNPELAJARAN 2024/2025 - Rianti, Ketut Dian; Indrawati, IGA Putu Tuti; Suparsa, I Nyoman (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2025)
This study is a class action research (CAR) which aims to: 1) to find out the improvement of the writing skills of observation report texts of students in grade VIII.6 of SMP Negeri 7 Denpasar after using the Think Talk Write type cooperative learning model assisted by image media, 2) to find out the steps to implement the Think Talk Write type cooperative learning model assisted by image media in improving the skill soft writing Observation Report Texts, 3) and to find out the responses of students ingrade VIII.6 SMP Negeri 7 Denpasar on the application of the Think Talk Write type cooperative learning model assisted by image media in improving the skill of writing observation report texts. Data collection was carried out by writing tests, observations, questionnaires, and documentation. The data that has been obtained are analyzed by qualitative and quantitative descriptive analysis methods. The results of the study show that the application of the Think Talk Write model assisted by image media can improve students’ writing skills, especially in critical thinking, discussion, and systematic text composition. In the initial test, the average score of students was 73.39 with the Minimum Completeness Criteria (MCC) of 21.95%, which increased to 81.51 with aMCC of 39.02% in the first cycle. The increase continued until it reached 91.95 with aMCC of 100% in the second. This improvement in writing skills is driven by learning steps, namely: 1) Think, students make observations on the image provided and identify important information related to the object being observed. 2) Talk, students discuss the results of their observations in small groups to develop understanding and formulate main ideas. 3) Write, students pour the results of the discussion into the form of a text report on the results of observations systematically in accordance with applicable linguistic rules. The students’ response to this learning model was very positive, with 77.07% of students stating that they strongly agreed and 22.93% agreed, while no students disagreed or strongly disagreed. This research makes an important contribution to the development of Indonesian learning, especially in improving the skill of writing observation report texts at the junior high school level. Abstrak Penelitian ini merupakan penelitian tindakan kelas (PTK) yang bertujuan: 1) untuk mengetahui peningkatan keterampilan menulis teks laporan hasil observasi siswa kelas VIII.6 SMP Negeri 7 Denpasar setelah menggunakan model pembelajaran kooperatif tipe Think Talk Write berbantuan media gambar, 2) untuk mengetahui langkah-langkah penerapan model pembelajaran kooperatif tipe Think Talk write berbantuan media gambar dalam peningkatan keterampilan menulis teks Laporan HasilObservasi, 3) serta untuk mengetahui respons siswa kelas VIII.6 SMP Negeri 7 Denpasar terhadap penerapan model pembelajaran kooperatif tipe Think Talk Write berbantuan media gambar dalam meningkatkan keterampilan menulis teks laporan hasil observasi. Pengumpulan data dilakukan dengan tes menulis, observasi,angket/kuesioner, dan dokumentasi. Data yang telah diperoleh dianalisis dengan metode analisis deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa penerapan model Think Talk Write berbantuan media gambar dapat meningkatkan keterampilan menulis siswa, terutama dalam berpikir kritis, berdiskusi, dan menyusun teks secara sistematis. Pada tes awal, nilai rata-rata siswa adalah 73,39 dengan Kriteria Ketuntasan Minimal (KKM) sebesar 21,95%, yang meningkat menjadi 81,51 dengan KKM 39,02% pada siklus I. Peningkatan terus berlanjut hingga mencapai 91,95 dengan KKM sebesar 100% pada siklus II. Peningkatan keterampilan menulis ini didorong oleh langkah-langkah pembelajaran, yaitu: 1) Think (berpikir), siswa melakukan observasi terhadap gambar yang disediakan dan mengidentifikasi informasi penting terkait objek yang diamati. 2) Talk (berbicara), siswa mendiskusikan hasil observasinya dalam kelompok kecil untuk mengembangkan pemahaman dan merumuskan ide-ide utama. 3) Write (menulis), siswa menuangkan hasil diskusi kedalam bentuk teks laporan hasil observasi secara sistematis sesuai dengan kaidah kebahasaan yang berlaku. Respons siswa terhadap model pembelajaran ini sangat positif, dengan 77,07% siswa menyatakan sangat setuju dan 22,93% setuju, sementaratidak ada siswa yang tidak setuju atau sangat tidak setuju. Penelitian ini memberikan kontribusi penting bagi pengembangan pembelajaran Bahasa Indonesia, khususnya dalam meningkatkan keterampilan menulis teks laporan hasil observasi di tingkat SMP.